If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 46 = 2x Reorder the terms: 46 + x = 2x Solving 46 + x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 46 + x + -2x = 2x + -2x Combine like terms: x + -2x = -1x 46 + -1x = 2x + -2x Combine like terms: 2x + -2x = 0 46 + -1x = 0 Add '-46' to each side of the equation. 46 + -46 + -1x = 0 + -46 Combine like terms: 46 + -46 = 0 0 + -1x = 0 + -46 -1x = 0 + -46 Combine like terms: 0 + -46 = -46 -1x = -46 Divide each side by '-1'. x = 46 Simplifying x = 46
| 2c-(c+6)=4(a-2) | | (10+i)-(3-5i)=0 | | -6x+2x=-7-4x+x | | 9.6x+63.18=-10.4x+61.54 | | 120=x+3x | | -27=3(4x+3) | | 35x+3x-9=180 | | (-8+5m)(5)= | | 42x/70x= | | -m^2-9m=-5m+10 | | 7.1x-1.2=20.1 | | -10-3b=b+6 | | 4x+6x=132 | | 30/r=5 | | 5x-4(2x-7)=13 | | 6(4z-1)-3(z+9)=14(z+1) | | 3x+(x+18)=90 | | -6k+7k+5=-5+3k | | -4(t-4)-(t+3)=8 | | 2x+(x+78)=180 | | 7+6(x-2)=9-2(x-9) | | -3.33=.50x | | x+3(-x-6)=-18 | | 12x^2-360x+2025=0 | | -3.33=-.50 | | 3=lnx+ln(x+2) | | (5c+3)(3c-5)= | | ly+3l=17 | | -6-7v=-6(4v+1) | | 8x+133=15x | | -4b-40=2(-4b-8)+4 | | C=2.75p+3.00 |